When the Shooting Stopped: Crisis Negotiation and Critical Incident Change - Charlés, Laurie L., (Rowman & Littlefield Publishers, 2007)
CharlZs outlines a fundamental methodology for crisis negotiation, as it occurs for law-enforcement officers trained in crisis intervention. When the Shooting Stopped systematically examines the process of negotiation, dissecting the conduct of meaningful discourse, use of language, and use of the collaborative team process. Using case data on a school hostage negotiation, CharlZs reveals the underlying communication processes at work in crisis negotiation. When the Shooting Stopped is a key resource for criminal justice professionals, law enforcement personnel, and family counseling psychologists alike.